Argentina: a case study on the Plan Jefes y Jefas de Hogar Desocupados, or the employment road to economic recovery - Daniel Kostzer (Levy Economics Institute of Bard College, 2008)
After the 2001 crisis, Argentinaonce the poster-child for pro-market structural-adjustment policieshad to define a new strategy in order to manage the societal demands that had led to the fall of the previous administration. The demand by the majority of the population for employment recovery spurred the government to introduce a massive employment program, the Plan Jefes y Jefas de Hogar Desocupados (Program for Unemployed Male and Female Heads of Households). This program, which accounted for less than 1 percent of GDP at the outset, paved the way for a reduction of the contractionary effects that otherwise would have caused a catastrophic devaluation of the currency. This paper explores how Argentina pursued a strategy of employment generation, with the state participating as employer of last resort, to recover from one of the worst social and economic crises in its history.
Keywords: H53; J08; J48; 330; Argentina; Employment; Employer of Last Resort (ELR); Economic Growth; Fiscal Policies; Social Policies